The Effect of the Ketogenic Diet on Weight Loss and Metabolic Risk Factors: A Systematic Review and Meta-Analysis - Intan Lestari Putri; I Wayan Weta (Syntax Corporation Indonesia, 2025)
Obesity remains a major global health problem with increasing prevalence, leading to a rise in the use of dietary interventions such as the ketogenic diet. Despite its popularity, evidence regarding its effectiveness in improving metabolic parameters remains inconsistent. This study aimed to evaluate the impact of the ketogenic diet on weight loss and metabolic risk factors through a systematic review and meta-analysis. Following the PRISMA 2020 guidelines, relevant studies were retrieved from PubMed, ScienceDirect, Cochrane Library, and ProQuest databases. Eligible randomized controlled trials assessing the effects of the ketogenic diet on glucose control, blood pressure, body mass index (BMI), and lipid profiles in obese patients were included. Data extraction and quality assessment were conducted using the Risk of Bias (RoB) tool, and statistical analyses were performed with Review Manager v5.3. Nine eligible studies (n = 437 participants) were included. The ketogenic diet significantly reduced blood glucose levels (SMD = -0.27 mg/dL, 95% CI: -0.50 to -0.04, P = 0.02) and triglycerides (SMD = -28.38 mg/dL, 95% CI: -32.07 to -24.69, P < 0.001), while increasing LDL cholesterol (SMD = 17.27 mg/dL, 95% CI: 1.10 to 33.44, P = 0.04). However, no significant changes were observed in BMI, HDL, total cholesterol, or blood pressure. Funnel plot and Egger’s test results indicated no publication bias. In conclusion, the ketogenic diet demonstrates beneficial effects on glucose regulation and triglyceride reduction but has limited efficacy for weight loss and may elevate LDL levels, warranting cautious clinical application in obesity management.